Growth of HIV-exposed infants from birth to 6 months in the prevention of mother-to-child transmission program - Maria Priskila; Ketut Dewi Kumarawati; Ni Putu Siadi Purniti (Paediatrica Indonesiana, 2019)
Background Human immunodeficiency virus (HIV) infection is a global health issue. Most cases of HIV infection in children are acquired through transmission from HIV-infected mothers. Maternal HIV infection affects infant growth. Objective To evaluate the first six months of growth in HIV-exposed infants born to mothers in the prevention of mother-to-child transmission (PMTCT) program. Methods This prospective cohort study was done in 40 HIV-exposed infants born in Sanglah General Hospital, Bali. Subjects' underwent weight and length measurements at birth and monthly for 6 months. Data analyses used were repeated ANOVA test with Bonferonni post-hoc analysis for normally distributed data and Friedman test with Wilcoxon post-hoc analysis for abnormally distributed data. Correlations between birth weight and length to weight and length at 6 months of age were analyzed with Spearman's test. Results Subjects' mean birth weight was 2,900 (SD 546) grams and median birth length was 48 (range 36-52) cm. Subjects' body weight and length increased monthly throughout the measurement period (P<0.001). There was a strong negative correlation between birth weight and infant weight gain at 6 months of age (r=-0.678), and a moderate negative correlation between birth length and infant length gain at 6 months of age (r=-0.564). Conclusion HIV-exposed infants born to mothers in the PMTCT program have a significant body weight and body length growth in the first 6 months of life, and followed general WHO weight and length curves for age.